Narrative, positionality, and pedagogy: an exploration of the classroom narrative - Enoch, Jennifer, author; Gage, Scott, advisor; Souder, Donna, committee member; Eskew, Doug, committee member; Pettit, Sue, committee member (Colorado State University. Libraries, 2013)
Narrative writing has become an integral part of scholarship in the field of rhetoric and composition, particularly in the area of composition pedagogy. This thesis identifies and interrogates the classroom narrative, a form of scholarly, narrative writing that narrates classroom events in order to persuade its reader to adopt, reject, or think critically about its author's pedagogy. This thesis argues that, in order to accomplish this purpose, the author of the classroom narrative employs a persuasive process in which she deliberately uses postionality, the process of articulating the author's identity in the text, to persuade the reader to invest in her pedagogy. At the same time, she uses the text's narrative features to reinforce the reader's understanding of her pedagogy. The result is that the persuasive use of postionality and the text's narrative features combine to advance a pedagogical argument and create pedagogical knowledge. In order to illustrate this persuasive process, two classroom narratives will be analyzed: "Understanding Problems in the Critical Classroom" by William H. Thelin and "The American Scholar Writes the New 'Research' Essay" by Jackie Grutsch McKinney. The classroom narrative's persuasive process - both its use of positionality and its reliance on narrative features - has implications for the way that positionality is conceived of and for how pedagogical knowledge is created through narrative.